If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6)(x + 3) = 340 Reorder the terms: (6 + x)(x + 3) = 340 Reorder the terms: (6 + x)(3 + x) = 340 Multiply (6 + x) * (3 + x) (6(3 + x) + x(3 + x)) = 340 ((3 * 6 + x * 6) + x(3 + x)) = 340 ((18 + 6x) + x(3 + x)) = 340 (18 + 6x + (3 * x + x * x)) = 340 (18 + 6x + (3x + x2)) = 340 Combine like terms: 6x + 3x = 9x (18 + 9x + x2) = 340 Solving 18 + 9x + x2 = 340 Solving for variable 'x'. Reorder the terms: 18 + -340 + 9x + x2 = 340 + -340 Combine like terms: 18 + -340 = -322 -322 + 9x + x2 = 340 + -340 Combine like terms: 340 + -340 = 0 -322 + 9x + x2 = 0 Factor a trinomial. (-23 + -1x)(14 + -1x) = 0Subproblem 1
Set the factor '(-23 + -1x)' equal to zero and attempt to solve: Simplifying -23 + -1x = 0 Solving -23 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + -1x = 0 + 23 Combine like terms: -23 + 23 = 0 0 + -1x = 0 + 23 -1x = 0 + 23 Combine like terms: 0 + 23 = 23 -1x = 23 Divide each side by '-1'. x = -23 Simplifying x = -23Subproblem 2
Set the factor '(14 + -1x)' equal to zero and attempt to solve: Simplifying 14 + -1x = 0 Solving 14 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -1x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = 0 + -14 -1x = 0 + -14 Combine like terms: 0 + -14 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14Solution
x = {-23, 14}
| 4(a+3)=2a-12 | | -25d+2s-7+15s-20d= | | -11a^2b*8ab= | | 7x+14-2x-5=3x | | 7x+14-2x-5=3x | | 5a*a^2= | | 2(x+6)=9x+9-7x+3 | | 3a^2-3a= | | 20j+20j-16m-16m+16= | | 6k-(4k+2)-8+8(2k+2)=0 | | x-5=28 | | 6k-(2k+2)-8+8(2k+2)=10 | | 6k-(4k+2)-8+8(2k+2)=10 | | 10+(-4g)+10-13x-2g+5x= | | 2.75=f-.25 | | 3x-15+10x=13x+20 | | 5y+7=1-7y | | -19m+5-(-m)+c-7c= | | 7x-4+3x+12= | | 7x-4+3x+12=30 | | 3x+(-17)+21f+3x-(-21f)= | | 3y-20+y+40=120 | | 3y-20+y+40=180 | | 3y-20+y+40=90 | | 3y-20+y+40=30 | | 3x-20+x+10=30 | | 3(3m-4)-(2m-3)=m+9 | | 3x-20+x+10=90 | | 3x-20+x+10= | | 2(-1)+1= | | 6k-4k=6 | | 7t-14-16t+9c+(-14c)= |